Evidence from Iraqi Banks on the Reporting of Sustainability Determinants and Their Impact on Market Returns - Al Kaab, Amal Fadhil Akho Bashah; Wahhab, Asaad Mohammed Ali (Technium Social Sciences Journal, 2023)
The objective of this study is to define the concept of sustainability, its dimensions, and the importance of reporting it; to measure the level of reporting on the dimensions of sustainability for banks listed on the Iraq Stock Exchange; and to determine the effect of the level of reporting on market returns and the cost of equity financing. A sample of commercial banks registered on the Iraqi market was chosen for the study objective. The study relied on the applied side of the employment of environmental, social, and governance (ESG) indicators and the standards of the Global Reporting Initiative (GRI) to analyze the content of the reports of the commercial banks and to determine the extent of their commitment to reporting on the dimensions of sustainability. Commercial banks issued ten (10) securities during the period (2016–2021). The market returns of shares were calculated using the annual closing and opening share prices. Between weak and very weak, the general average level of reporting information related to the economic pillar was 34.22. In comparison, it was 7.23 for the environmental and 15.70 for the social pillars. The governance axis had a reporting rate of 24.95%, while the average reporting rate for other public disclosures was 43.72%. The study also uncovered a direct and statistically significant relationship between the market returns of the study sample institutions’ shares and the dimensions of sustainability.